Repair of Ni-based single-crystal superalloys using vacuum plasma spray. (15th April 2019) - Kalfhaus, T.; Schneider, M.; Ruttert, B.; Sebold, D.; Hammerschmidt, T.; Frenzel, J.; Drautz, R.; Theisen, W.; Eggeler, G.; Guillon, O.; Vassen, R.
Abstract: Turbine blades in aviation engines and land based gas-turbines are exposed to extreme environments. They suffer damage accumulation associated with creep, oxidation and fatigue loading. Therefore, advanced repair methods are of special interest for the gas-turbine industry. In this study, CMSX-4 powder is sprayed by Vacuum Plasma Spray (VPS) on single-crystalline substrates with similar compositions. The influence of the substrate temperature is investigated altering the temperature of the heating stage between 850 °C to 1000 °C. Different spray parameters were explored to identify their influence on the microstructure. Hot isostatic pressing (HIP) featuring fast quenching rates was used to minimize porosity and to allow for well-defined heat-treatments of the coatings. The microstructure was analysed by orientation imaging scanning electron microscopy (SEM), using electron backscatter diffraction (EBSD). The effects of different processing parameters were analysed regarding their influence on porosity and grain size. The results show that optimized HIP heat-treatments can lead to dense coatings with optimum γ/γ′ microstructure. The interface between the coating and the substrate is oxide free and shows good mechanical integrity. The formation of fine crystalline regions as a result of fast cooling was observed at the single-crystal surface, which resulted in grain growth during heat-treatment in orientations determined by the crystallography of the substrate. Graphical abstract: Unlabelled Image Highlights: Vacuum plasma spray is used for the deposition of CMSX-4 powder on heated single crystalline CMSX-4 substrates. Coatings with different spray parameters were produced to identify the condition for optimum mechanical properties. A HIP is used to promote grain growth, decrease the porosity and achieve the desired microstructure. The microstructure of the interface region and the coating was characterised in the as-spayed and the HIP condition.